Religion and state in Iran 1785-1906 : the role of the Ulama in the Qajar period - Algar, Hamid, 1940- (Berkeley : University of California Press, 2020)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1969.
X Mlrzà Husayn Khan Sipahsalàr and his Downfall -- XI. Two Apostles of Change and the Ulama -- XII. The Repeal of the Tobacco Concession and Its Consequences -- XIII. The Clerical Opposition to Amīn ucUDaula and Amīn us-Sultān (1896-1903) -- XIV. The Ulama and the Early Constitutional Movement -- XV. Conclusion -- Glossary -- Bibliography -- Index
Facsimile reproduction of original published in 1969. Publication date taken from publishers' website.
Ten digit ISBN taken from original publication.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Clergy -- Political activity -- Iran; Iran -- History -- Qajar dynasty, 1794-1925.; Clergé -- Activité politique -- Iran; Iran -- Histoire -- 1794-1925 (Dynastie des Qādjārs); RELIGION / Islam / General; Clergy -- Political activity; Qajar Dynasty (Iran); Iran; Electronic books; History